Nanocomposite structural color hydrogel and preparation method and application thereof
Patent Information
- Application Number
- CN202310631690.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-05-31
AI Technical Summary
可穿戴电子器件构造复杂,且其中坚硬的硅半导体材料与柔软的有机体不兼容
[0020]1、采用一步原位凝胶化方法制备结构色纳米复合水凝胶,具有制备效率高、易放大等优点。而传统的纳米复合材料通常采用模板法(包含模板的组装、功能聚合物材料的填充,或者包含移除模板步骤等多步),制备步骤复杂,难以批量制备。
Smart Images

Figure CN116655951B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wearable sensor technology, and in particular to a nanocomposite structured color hydrogel, its preparation method, and its application. Background Technology
[0002] Smart structural color materials have shown great application potential in the field of sensing (JMWeissman,HBSunkara,ASTse,SAAsher,Science 1996,274,959;JPGe,YDYin,Angew.Chem.Int.Ed.2011,50,1492;ZYCai,DHKwak,D.Punihaole,ZMHong,SSVelankar,XYLiu,SAAsher,Angew.Chem.Int.Ed.2015,54,13036;F.Meng,B.Ju,Z.Wang,R.Han,Y.Zhang,S.Zhang,P.WuandB.Tang,J.Am.Chem.Soc.,2022,144,7610-7615). However, the mechano-induced color-changing properties of traditional nanocomposite structural color materials and structural color changes caused by other special stimuli interfere with each other, severely affecting the signal output of non-deformation sensors and thus severely limiting the development of non-deformation wearable sensors. Due to this limitation, current wearable sensors based on nanocomposite structural color materials are limited to sensing and monitoring material deformation caused by heartbeats, joint movements, etc. (Y.Wang, LRShang, GPChen, LYSun, XXZhang, YJZhao, Sci.Adv.2020, 6, eaax8258; HYTan, QQLyu, ZJXie, MMLi, K.Wang, K.Wang, BJXiong, LBZhang, JTZhu, Adv.Mater.2019, 31, e1805496). Eliminating the influence of mechanical deformation on the optical signal output of wearable sensors is an important prerequisite for the development of non-deformation wearable structural color sensors. Existing technologies (P. Han, XY He, YX Zhang, HY Zhou, MJ Liu, N. Wu, JK Jiang, Y. Wei, X. Yao, JM Zhou, YLSong, Adv. Optical Mater. 2019, 7, 1801749) have previously used hierarchical optical structure design to prepare nanocomposite organic gel materials whose structural colors remain stable under various extreme mechanical deformation conditions, laying an important foundation for the development of wearable sensors. However, further endowing this material with intelligent response properties still faces considerable challenges.
[0003] Hydrogel materials possess physicochemical properties similar to human tissue and are widely used in wearable sensing. However, their current applications are primarily in wearable electronic sensors (HWYuk, BYLu, XHZhao, Chem. Soc. Rev. 2019, 48, 1642; LXHu, PLChee, S. Sugiarto, Y. Yu, CQShi, R. Yan, ZQYao, XWShi, JCZhi, D. Kai, HDYu, W. Huang, Adv. Mater. 2022, e2205326.). Wearable electronic devices have complex structures, and the rigid silicon semiconductor materials within them are incompatible with soft organic matter. Therefore, developing a wearable gel sensor with a simple structure, convenient preparation method, safety, environmental friendliness, and non-invasiveness, using tunable structural color as an indicator signal, has significant application value. Summary of the Invention
[0004] The purpose of this invention is to provide a nanocomposite structural color hydrogel, its preparation method, and its application. The nanocomposite structural color hydrogel can eliminate the interference of mechanical deformation on the optical signal output of the hydrogel sensor. At the same time, it can realize wearable sensing and monitoring of the intensity of the above-mentioned stimuli by the change in structural color caused by changes in external stimuli (such as temperature, pH, glucose, etc.). Moreover, it is simple in construction, easy to prepare, safe, green, and non-invasive.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] This invention provides a method for preparing a nanocomposite structured color hydrogel, comprising the following steps:
[0007] Monodisperse nanoparticles were dispersed in water, and the resulting monodisperse nanoparticle dispersion was mixed with hydrogel monomers and sheet-like nanoclays, and then in-situ gelled to obtain a nanocomposite structured colored hydrogel.
[0008] Preferably, the monodisperse nanoparticles include one of monodisperse polystyrene latex particles, monodisperse polymethyl methacrylate latex particles, monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles, monodisperse silica particles, monodisperse iron oxide particles, monodisperse carbon spheres, and monodisperse titanium dioxide particles, wherein the particle size of the monodisperse nanoparticles is 120–500 nm; and the mass fraction of the monodisperse nanoparticle dispersion is 1–20%.
[0009] Preferably, the hydrogel monomer is acrylamide, isopropylacrylamide, acrylamide containing terminal phenylboronic acid functional groups, acrylic acid, or animal gelatin; the mass ratio of the hydrogel monomer to the monodisperse nanoparticles is 0.3:1 to 1:1.
[0010] Preferably, the sheet-like nanoclay includes one or more of kaolinite, attapulgite, lithium montmorillonite, diatomite, illite, sepiolite, and lithium diatomite; the sheet size of the sheet-like nanoclay is 5-100 nm, and the thickness is 1-10 nm; the mass of the sheet-like nanoclay is 20-200% of the mass of the hydrogel monomer.
[0011] Preferably, the mixing further includes the addition of black nanoparticles; the black nanoparticles are one of carbon black nanoparticles, iron oxide nanoparticles, dopamine nanoparticles, melanin nanoparticles, graphene nanosheets, carbon nanotubes, metal particles and polypyrrole nanoparticles, the size of the black nanoparticles is 5-80 nm, and the mass of the black nanoparticles is 0.1-2% of the mass of the monodisperse nanoparticles.
[0012] Preferably, when the hydrogel monomer is one or more of acrylamide, isopropylacrylamide, acrylamide containing terminal phenylboronic acid functional groups, and acrylic acid, the mixing further includes the addition of an initiator and a catalyst.
[0013] Preferably, the initiator is one or more of ammonium persulfate, potassium persulfate, sodium persulfate, azobisisobutyronitrile, and benzoyl peroxide; the mass of the initiator is 0.1-3% of the mass of the hydrogel monomer; the catalyst is one or more of tetramethylethylenediamine, tetraethylethylenediamine, tetramethylpropylenediamine, and tetraethylpropylenediamine; the mass of the catalyst is 0.005-0.05% of the mass of the hydrogel monomer.
[0014] Preferably, the in-situ gelation temperature is 4–40°C and the time is 20–40 h.
[0015] The present invention provides a nanocomposite structured color hydrogel prepared by the preparation method described above, comprising a hydrogel framework, monodisperse nanoparticles and sheet-like nanoclay, wherein the monodisperse nanoparticles and sheet-like nanoclay are distributed in a random and loose manner in the hydrogel framework.
[0016] This invention provides the application of the nanocomposite structured color hydrogel described above in the field of wearable sensors.
[0017] This invention provides a method for preparing a nanocomposite structural color hydrogel. The method employs in-situ gelation to lock the arrangement of monodisperse nanoparticles in a dispersion, resulting in a novel, unassembled, randomly loose optical structure. The random spacing of the monodisperse nanoparticles in this structure eliminates the influence of mechanical deformation on their arrangement, thus ensuring the stability of the structural color under mechanical deformation. This avoids interference from mechanical deformation on the optical signal output of the hydrogel sensor. Furthermore, by sensing changes in the structural color caused by external stimuli (such as temperature, pH, and glucose), wearable sensing and monitoring of the intensity of these stimuli can be achieved. In contrast, traditional methods relying on close-packed, loosely packed, and inverse opal structures obtained through nanoparticle assembly do not possess the property of maintaining stable structural color under deformation.
[0018] The nanocomposite structural color hydrogel prepared by this invention can cause changes in the arrangement of nanoparticles locked by the hydrogel itself due to different skeleton properties. The obvious color change can be used to sense and monitor biological information such as temperature, pH, glucose, and lactic acid in real time. The wavelength range of the color change caused by the above-mentioned stimulus intensity change is 480-670nm; within the range of 300% tensile deformation, the wavelength shift of the structural color is between 1-15nm.
[0019] The beneficial effects of this invention are:
[0020] 1. The one-step in-situ gelation method for preparing structural color nanocomposite hydrogels has advantages such as high preparation efficiency and easy scale-up. In contrast, traditional nanocomposite materials usually adopt template methods (including template assembly, functional polymer material filling, or multiple steps such as template removal), which are complex to prepare and difficult to mass-produce.
[0021] 2. The unique property of structural color in in-situ gelled and locked random loose nanoparticles, resulting in an unassembled structure, is unaffected by mechanical deformation, thus avoiding interference with signal output and enabling its application in wearable sensors. In contrast, the structural color of traditional structural color hydrogels is easily affected by mechanical strain.
[0022] 3. The macroscopic volume changes caused by the response of the hydrogel framework to external stimuli (such as temperature, pH, and glucose) and the macroscopic color changes caused by the influence of the nanoparticle structure endow nanocomposite hydrogels with wearable sensing properties, pointing the way for the development of wearable photonic platforms.
[0023] 4. Nanocomposite structured color hydrogels can be endowed with high mechanical strength and self-healing properties through dynamic physical cross-linking and hydrogen bonding. The self-healing properties help to work stably for a long time and improve the service life of wearable sensors. Attached Figure Description
[0024] Figure 1 Transmission electron microscope (TEM) images of the nanocomposite structured colored hydrogels prepared for Examples 1(A) and 2(B);
[0025] Figure 2 The images show the nanocomposite structured color hydrogel prepared in Example 2 under tensile and compressive conditions; where A is a digital photograph of the sample with tensile deformation of 0%, 250%, and 500% (from top to bottom → from left to right), and B is a digital photograph of the sample with compressive deformation of 0%, 70%, and 90% (from top to bottom).
[0026] Figure 3 Photographs of the nanocomposite structured color hydrogel prepared in Example 3 at different temperatures;
[0027] Figure 4 The reflectance spectra of the nanocomposite colored hydrogel prepared in Example 3 after absorbing water and swelling were measured at different temperatures.
[0028] Figure 5 The reflectance spectra of the nanocomposite structured colored hydrogel prepared in Example 3 after absorbing water and swelling under different tensile deformation states are shown. Detailed Implementation
[0029] This invention provides a method for preparing a nanocomposite structured color hydrogel, comprising the following steps:
[0030] Monodisperse nanoparticles were dispersed in water, and the resulting monodisperse nanoparticle dispersion was mixed with hydrogel monomers and sheet-like nanoclays, and then in-situ gelled to obtain a nanocomposite structured colored hydrogel.
[0031] In this invention, unless otherwise specified, the raw materials required for preparation are all commercially available products well known to those skilled in the art or synthesized according to disclosed methods.
[0032] In this invention, the monodisperse nanoparticles preferably include one of the following: monodisperse polystyrene latex particles, monodisperse polymethyl methacrylate latex particles, monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles, monodisperse silica particles, monodisperse iron oxide particles, monodisperse carbon spheres, and monodisperse titanium dioxide particles. The particle size of the monodisperse nanoparticles is preferably 120–500 nm, more preferably 195–250 nm, and even more preferably 210–220 nm. In this invention, the function of the monodisperse nanoparticles is to induce structural color through resonant Mie scattering.
[0033] The present invention does not have any particular limitation on the dispersion of monodisperse nanoparticles in water; a uniform dispersion can be obtained by following a process well known in the art.
[0034] The present invention preferably involves sequentially adding hydrogel monomer, sheet-like nanoclay, initiator and catalyst to the monodisperse nanoparticle dispersion.
[0035] In this invention, the mass fraction of the monodisperse nanoparticle dispersion is preferably 1-20%, more preferably 5-15%, and even more preferably 10%.
[0036] In this invention, the hydrogel monomer is preferably one or more of acrylamide, isopropylacrylamide, acrylamide with terminal phenylboronic acid functional groups, acrylic acid, and animal gelatin; the terminal phenylboronic acid functional group is preferably 3-fluoro-4-methylcarbamoylphenylboronic acid; and the animal gelatin is preferably pigskin gelatin or fish skin gelatin. When the hydrogel monomer is two or more of the above, this invention does not have a special limitation on the ratio of different types of hydrogels, and can be adjusted according to actual needs.
[0037] In this invention, the mass ratio of the hydrogel monomer to the monodisperse nanoparticles is preferably 0.3:1 to 1:1, and more preferably 1:1.
[0038] In this invention, the sheet-like nanoclay preferably includes one or more of kaolinite, attapulgite, lithium montmorillonite, diatomite, illite, sepiolite, and lithium diatomite. The sheet size of the sheet-like nanoclay is preferably 5–100 nm, more preferably 10–80 nm, and even more preferably 15–30 nm; the thickness is preferably 1–10 nm. When the sheet-like nanoclay is two or more of the above-mentioned types, this invention does not have a special limitation on the ratio of different types of sheet-like nanoclay, and can be adjusted according to actual needs. This invention utilizes sheet-like nanoclay as a physical crosslinking agent, with its surface as a reaction site, to induce the polymerization of hydrogel monomers on its surface, forming a homogeneous hydrogel network, thus endowing the hydrogel with excellent mechanical, optical, and responsive properties.
[0039] In this invention, the mass of the sheet-like nanoclay is preferably 20-200% of the mass of the hydrogel monomer, more preferably 100%.
[0040] In this invention, when the monodisperse nanoparticles are not black, the mixing process preferably includes adding black nanoparticles; when the monodisperse nanoparticles are black, it is not necessary to add black nanoparticles. The black nanoparticles are preferably one of carbon black nanoparticles, iron oxide nanoparticles, dopamine nanoparticles, melanin nanoparticles, graphene nanosheets, carbon nanotubes, metal particles, and polypyrrole nanoparticles. The carbon nanotubes are preferably single-walled or multi-walled carbon nanotubes. The metal particles are preferably Fe, Ag, or Cu. The size of the black nanoparticles is preferably 5–80 nm, more preferably 10–20 nm. The size of the black nanoparticles preferably represents particle size, tube diameter, or sheet size, and can be set according to the above size range based on actual needs. This invention utilizes black nanoparticles to absorb multiple scattered light, thereby improving the color saturation of the hydrogel structural color.
[0041] In this invention, the mass of the black nanoparticles is preferably 0.1-2% of the mass of the monodisperse nanoparticles, more preferably 0.3-0.5%. When adding black nanoparticles, this invention preferably adds hydrogel monomer, sheet-like nanoclay, black nanoparticles, initiator, and catalyst sequentially to the monodisperse nanoparticle dispersion.
[0042] In this invention, when the hydrogel monomer is one or more of acrylamide, isopropylacrylamide, acrylamide containing terminal phenylboronic acid functional groups, and acrylic acid, the mixing preferably further includes the addition of an initiator and a catalyst; when the hydrogel monomer is animal gelatin, the gelatin itself forms a gel, and no initiator or catalyst is required.
[0043] In this invention, the initiator is preferably one or more of ammonium persulfate, potassium persulfate, sodium persulfate, azobisisobutyronitrile, and benzoyl peroxide. When the initiator is two or more of the above, this invention does not have a special limitation on the ratio of different types of initiators, and can be adjusted according to actual needs. The mass of the initiator is preferably 0.1-3% of the mass of the hydrogel monomer. This invention utilizes the initiator to initiate cross-linking reactions between hydrogel monomers and between hydrogel monomers and nano-clay to form a hydrogel network.
[0044] In this invention, the catalyst is preferably one or more of tetramethylethylenediamine, tetraethylethylenediamine, tetramethylpropylenediamine, and tetraethylpropylenediamine; when the catalyst is two or more of the above, this invention does not have a special limitation on the ratio of different types of catalysts, and can be adjusted according to actual needs; the mass of the catalyst is preferably 0.005-0.05% of the mass of the hydrogel monomer, more preferably 0.01%. This invention utilizes a catalyst to improve the efficiency of forming a hydrogel network.
[0045] In this invention, the temperature of in-situ gelation is preferably 4 to 40°C, more preferably 25°C, and the time is preferably 20 to 40 hours, more preferably 36 hours.
[0046] After completing the in-situ gelation, the present invention preferably obtains a nanocomposite structural color hydrogel directly without post-processing; the nanocomposite structural color hydrogel is preferably a block copolymer of one or more of the following: polyacrylamide structural color hydrogel, polyisopropylacrylamide structural color hydrogel, polyacrylic acid structural color hydrogel, gelatin structural color hydrogel, and polyacrylamide structural color hydrogel containing terminal phenylboronic acid functional groups.
[0047] The present invention provides a nanocomposite structured color hydrogel prepared by the preparation method described above, comprising a hydrogel framework, monodisperse nanoparticles and sheet-like nanoclay, wherein the monodisperse nanoparticles and sheet-like nanoclay are distributed in a random and loose manner in the hydrogel framework.
[0048] This invention provides the application of the nanocomposite structured color hydrogel described above in the field of wearable sensors. This invention does not specifically limit the method of application; the nanocomposite structured color hydrogel can be used as a sensor according to methods well-known in the art.
[0049] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0050] Example 1
[0051] Monodisperse silica nanoparticles with a particle size of 195 nm were dispersed in water to form a dispersion with a mass fraction of 10%. Isopropylacrylamide monomer (mass ratio of 1:1 to monodisperse nanoparticles) was dissolved in the above dispersion. Lithium montmorillonite (lamellae size 15 nm, thickness 1 nm) accounting for 100% of the mass fraction of isopropylacrylamide, carbon black nanoparticles (particle size 20 nm) accounting for 0.3% of the mass fraction of silica nanoparticles, ammonium persulfate accounting for 0.1% of the mass fraction of isopropylacrylamide, and tetramethylethylenediamine accounting for 0.01% of the mass fraction of isopropylacrylamide were added. In-situ gelation was carried out at 25 °C for 36 h to obtain a nanocomposite hydrogel with a structural color of blue.
[0052] Example 2
[0053] Monodisperse silica nanoparticles with a particle size of 250 nm were dispersed in water to form a dispersion with a mass fraction of 10%. Isopropylacrylamide monomer (mass ratio of 1:1 to monodisperse nanoparticles) was dissolved in the above dispersion. Kaolin (10 nm in size and 1 nm in thickness) was added at a mass fraction of 100% of the isopropylacrylamide, dopamine nanoparticles (20 nm in size) at a mass fraction of 0.1% of the silica nanoparticles, sodium persulfate at a mass fraction of 1% of the isopropylacrylamide, and tetraethylethylenediamine at a mass fraction of 0.05%. In-situ gelation was carried out at 4 °C for 40 h to obtain a nanocomposite hydrogel with a structural color of red.
[0054] Example 3
[0055] Monodisperse silica nanoparticles with a particle size of 210 nm were dispersed in water to form a dispersion with a mass fraction of 10%. Isopropylacrylamide monomer (mass ratio of 1:1 to monodisperse nanoparticles) was dissolved in the above dispersion. Attapulgite (lamellae size 15 nm, thickness 1 nm) accounting for 100% of the mass fraction of isopropylacrylamide, iron oxide nanoparticles (particle size 20 nm) accounting for 2% of the mass fraction of silica nanoparticles, potassium persulfate accounting for 3% of the mass fraction of isopropylacrylamide, and tetramethylpropylenediamine accounting for 0.005% of the mass fraction of isopropylacrylamide were added. In-situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of green.
[0056] Example 4
[0057] Monodisperse polystyrene latex particles with a particle size of 120 nm were dispersed in water to form a dispersion with a mass fraction of 1%. Acrylamide monomer (mass ratio of monodisperse nanoparticles of 0.3:1) was dissolved in the above dispersion. Diatomaceous earth (sheet size 5 nm, thickness 1 nm) accounting for 200% of the mass fraction of acrylamide, melanin nanoparticles (particle size 80 nm) accounting for 0.5% of the mass fraction of polystyrene latex particles, azobisisobutyronitrile (AIBN) accounting for 3% of the mass fraction of acrylamide, and tetraethylpropylene diamine accounting for 0.005% of the mass fraction of acrylamide were added. In-situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with a structure color of purple that responds to humidity.
[0058] Example 5
[0059] Monodisperse polymethyl methacrylate latex particles with a particle size of 500 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Pigskin gelatin (mass ratio of monodisperse nanoparticles of 1:1) was dissolved in the above dispersion. Sepiolite (sheet size 100 nm, thickness 10 nm) accounting for 100% of the mass fraction of pigskin gelatin and graphene nanosheets (size 10 nm) accounting for 0.5% of the mass fraction of polymethyl methacrylate latex particles were added. In-situ gelation was carried out at 4 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of red.
[0060] Example 6
[0061] Monodisperse carbon spheres with a particle size of 500 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Fish skin gelatin (mass ratio of monodisperse nanoparticles of 1:1) was dissolved in the above dispersion. Sepiolite (sheet size of 100 nm and thickness of 10 nm) accounting for 100% of the mass fraction of fish skin gelatin was added, and in-situ gelation was carried out at 4 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of red.
[0062] Example 7
[0063] Monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles with a particle size of 500 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Acrylic acid (mass ratio of monodisperse nanoparticles of 1:1) was dissolved in the above dispersion. Lithium diatomaceous earth (sheet size 100 nm, thickness 10 nm) accounting for 100% of the mass fraction of acrylic acid, single-walled carbon nanotubes (diameter 10 nm, length 100 nm) accounting for 0.5% of the mass fraction of monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles, azobisisobutyronitrile (3%) and a mixture of tetraethylpropylene diamine and tetramethylethylenediamine (mass ratio 1:1) accounting for 3% of the mass fraction of acrylic acid, were added. In situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of red.
[0064] Example 8
[0065] Monodisperse iron oxide particles with a particle size of 220 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Acrylic acid and acrylamide (total to monodisperse nanoparticle mass ratio of 1:1) were dissolved in the above dispersion. Lithium diatomaceous earth (sheet size 100 nm, thickness 10 nm) accounting for 100% of the total mass fraction of acrylic acid and acrylamide, azobisisobutyronitrile (3%) and a mixture of tetraethylpropylene diamine and tetramethylethylenediamine (mass ratio 1:1) accounting for 3% of the total mass fraction of acrylic acid and acrylamide, and in-situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with an orange structural color that responds to humidity and pH value.
[0066] Example 9
[0067] Monodisperse titanium dioxide particles with a particle size of 200 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Acrylic acid, acrylamide, and isopropylacrylamide (total mass ratio to monodisperse nanoparticles of 1:1:1) were dissolved in the above dispersion. Lithium diatomaceous earth (sheet size 100 nm, thickness 10 nm) accounting for 100% of the mass fraction of acrylic acid, acrylamide, and isopropylacrylamide, Ag nanoparticles (particle size 10 nm) accounting for 0.5% of the mass fraction of titanium dioxide particles, and a mixture of azobisisobutyronitrile (3% of the total mass fraction of acrylic acid, acrylamide, and isopropylacrylamide) and tetraethylpropylenediamine and tetramethylethylenediamine (mass ratio 1:1) accounting for 0.005% of the total mass fraction of acrylic acid, acrylamide, and isopropylacrylamide, was added. In situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with an orange structural color that responds to humidity, temperature, and pH value.
[0068] Example 10
[0069] Monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles with a particle size of 500 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Acrylic acid (mass ratio of monodisperse nanoparticles of 1:1) was dissolved in the above dispersion. Lithium diatomaceous earth (sheet size 100 nm, thickness 10 nm) accounting for 100% of the mass fraction of acrylic acid, Fe nanoparticles (particle size 10 nm) accounting for 0.5% of the mass fraction of monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles, azobisisobutyronitrile (3% of the mass fraction of acrylic acid), and a mixture of tetraethylpropylene diamine and tetramethylethylenediamine (mass ratio 1:1) accounting for 0.005% of the mass fraction of acrylic acid were added. In-situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of red.
[0070] Example 11
[0071] Monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles with a particle size of 500 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Acrylic acid (mass ratio of monodisperse nanoparticles of 1:1) was dissolved in the above dispersion. Lithium diatomaceous earth (sheet size 100 nm, thickness 10 nm) accounting for 100% of the mass fraction of acrylic acid, Cu nanoparticles (particle size 10 nm) accounting for 0.5% of the mass fraction of monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles, azobisisobutyronitrile (3% of the mass fraction of acrylic acid), and a mixture of tetraethylpropylene diamine and tetramethylethylenediamine (mass ratio 1:1) accounting for 0.005% of the mass fraction of acrylic acid were added. In-situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of red.
[0072] Example 12
[0073] Monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles with a particle size of 500 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Acrylic acid (mass ratio of monodisperse nanoparticles of 1:1) was dissolved in the above dispersion. Lithium diatomaceous earth (sheet size 100 nm, thickness 10 nm) accounting for 100% of the mass fraction of acrylic acid, polypyrrole nanoparticles (particle size 10 nm) accounting for 0.5% of the mass fraction of monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles, azobisisobutyronitrile (3% of the mass fraction of acrylic acid), and a mixture of tetraethylpropylene diamine and tetramethylethylenediamine (mass ratio 1:1) accounting for 0.005% of the mass fraction of acrylic acid were added. In-situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of red.
[0074] Example 13
[0075] Monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles with a particle size of 500 nm were dispersed in water to form a dispersion with a mass fraction of 20%. Acrylic acid (mass ratio of monodisperse nanoparticles of 1:1) was dissolved in the above dispersion. Lithium diatomaceous earth (sheet size 100 nm, thickness 10 nm) accounting for 100% of the mass fraction of acrylic acid, double-walled carbon nanotubes (diameter 2 nm, length 10 nm) accounting for 0.5% of the mass fraction of monodisperse poly(styrene-methyl methacrylate-acrylic acid) polymer latex particles, azobisisobutyronitrile (azobisisobutyronitrile) accounting for 3% of the mass fraction of acrylic acid, and a mixture of tetraethylpropylenediamine and tetramethylethylenediamine (mass ratio 1:1) accounting for 0.005%. In-situ gelation was carried out at 40 °C for 20 h to obtain a nanocomposite hydrogel with a structural color of red.
[0076] Characterization and performance testing
[0077] Figure 1Image A is a TEM image of the nanocomposite structured hydrogel prepared in Example 1, wherein the monodisperse silica nanoparticles have a particle size of 195 nm. Figure 1 It can be seen that monodisperse silica nanoparticles are distributed in a random and loose arrangement in the hydrogel holder, and the prepared nanocomposite hydrogel has a special random and loose optical structure.
[0078] Figure 1 Image B is a TEM image of the nanocomposite structured colored hydrogel prepared in Example 2, wherein the monodisperse silica nanoparticles have a particle size of 250 nm. Figure 1 It can be seen that monodisperse silica nanoparticles are distributed in a random and loose arrangement in the hydrogel holder, and the prepared nanocomposite hydrogel has a special random and loose optical structure.
[0079] Figure 2 The images show photographs of the nanocomposite structured colored hydrogel prepared in Example 2 under tensile and compressive conditions. A shows digital photographs of samples with tensile deformation of 0%, 250%, and 500% (from top to bottom, left to right), and B shows digital photographs of samples with compressive deformation of 0%, 70%, and 90% (from top to bottom). Figure 2 It is known that the structural color of hydrogels can remain stable under large deformation conditions.
[0080] Figure 3 The images show the nanocomposite structured color hydrogel prepared in Example 3 at different temperatures, from left to right: 30.6℃, 33.0℃, 33.3℃, 34.0℃, and 38.1℃. Figure 3 As shown, the green hydrogel turns red after absorbing water, and its structural color gradually changes to blue when the temperature is increased, indicating that the change in the structural color of the hydrogel can effectively reflect the change in temperature.
[0081] Figure 4 The reflectance spectra of the nanocomposite structured colored hydrogel prepared in Example 3 after absorbing water and swelling were measured at different temperatures. Figure 4 As shown, under different temperature conditions (30℃, 32℃, 33℃, 34℃, 35℃, 37℃ and 38℃), the wavelength range of color change caused by temperature variation is 480~670nm.
[0082] Figure 5 The reflectance spectra of the nanocomposite structured colored hydrogel prepared in Example 3 after water absorption and swelling are measured under different tensile deformation states. Figure 5 As shown, under different tensile deformation conditions (0, 300% and 500%), the wavelength range of color change caused by tensile deformation is 530-532nm, and the wavelength shift range of structural color is 2nm.
[0083] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a nanocomposite structured colored hydrogel, characterized in that, Includes the following steps: Monodisperse nanoparticles were dispersed in water, and the resulting monodisperse nanoparticle dispersion was mixed with hydrogel monomers and sheet-like nanoclays, and in-situ gelation was carried out to obtain a nanocomposite structured colored hydrogel. The monodisperse nanoparticles include one of the following: monodisperse polystyrene latex particles, monodisperse polymethyl methacrylate latex particles, monodisperse silica particles, monodisperse iron oxide particles, monodisperse carbon spheres, and monodisperse titanium dioxide particles. The hydrogel monomer is one or more of acrylamide, isopropylacrylamide, acrylamide with terminal phenylboronic acid functional groups, acrylic acid, and animal gelatin; the mass ratio of the hydrogel monomer to the monodisperse nanoparticles is 0.3:1 to 1:1; when the hydrogel monomer is one or more of acrylamide, isopropylacrylamide, acrylamide with terminal phenylboronic acid functional groups, and acrylic acid, the mixing further includes the addition of an initiator and a catalyst; The sheet-like nanoclay includes one or more of kaolinite, attapulgite, diatomite, illite, and sepiolite; the sheet size of the sheet-like nanoclay is 5~100nm, and the thickness is 1~10nm; the mass of the sheet-like nanoclay is 20~200% of the mass of the hydrogel monomer. The in-situ gelation temperature is 4~40℃, and the time is 20~40h; The nanocomposite structured color hydrogel includes a hydrogel framework, monodisperse nanoparticles, and sheet-like nanoclay, wherein the monodisperse nanoparticles and sheet-like nanoclay are distributed in a random and loose manner within the hydrogel framework.
2. The preparation method according to claim 1, characterized in that, The monodisperse nanoparticles have a particle size of 120~500nm; the mass fraction of the monodisperse nanoparticle dispersion is 1~20%.
3. The preparation method according to claim 1, characterized in that, The mixture also includes the addition of black nanoparticles; The black nanoparticles are one of carbon black nanoparticles, iron oxide nanoparticles, dopamine nanoparticles, melanin nanoparticles, graphene nanosheets, carbon nanotubes, metal particles, and polypyrrole nanoparticles. The size of the black nanoparticles is 5~80nm, and the mass of the black nanoparticles is 0.1~2% of the mass of the monodisperse nanoparticles.
4. The preparation method according to claim 1, characterized in that, The initiator is one or more of ammonium persulfate, potassium persulfate, sodium persulfate, azobisisobutyronitrile, and benzoyl peroxide; the mass of the initiator is 0.1-3% of the mass of the hydrogel monomer; the catalyst is one or more of tetramethylethylenediamine, tetraethylethylenediamine, tetramethylpropylenediamine, and tetraethylpropylenediamine; the mass of the catalyst is 0.005-0.05% of the mass of the hydrogel monomer.
5. The nanocomposite structured color hydrogel prepared by the preparation method according to any one of claims 1 to 4, characterized in that, It includes a hydrogel framework as well as monodisperse nanoparticles and sheet-like nanoclay, wherein the monodisperse nanoparticles and sheet-like nanoclay are distributed in a random and loose manner in the hydrogel framework.
6. The application of the nanocomposite structured color hydrogel of claim 5 in the field of wearable sensors.